HUBUNGAN SANITASI LINGKUNGAN DENGAN DEMAM BERDARAH DI PALOPO SULAWESI SELATAN - Musdalifah Syamsul; Yermi Yermi; Aminah Aminah; Fatmawati Fatmawati (UNM Environmental Journals, 2022)
Environmental sanitation issue of major importance to householders in rural areas a factor associated with Aedes aegypti abundance, so it takes efforts to overcome the spread of dengue disease, because dengue disease can cause danger of death. Dengue fever (DF) is a contagious disease and a relatively abbreviated time can be fatal if not treated immediately. Dengue fever are caused by dengue virus is transmitted through bite of Aedes aegypti. This study aims to know the associated of water storage container and prevention behaviour with dengue fever in Pontap, Palopo, Sulawesi Selatan. The study used observational (survey) with cross sectional approach. The sample used 88 houses, by random sampling, and the data was collected by direct interview using questionnaires and surveys. Analysis of research data used statistical yate's correction comparing the value X2 (3.84). The research result showed that the respondents who have water storage good and suffering dengue 9.7%, respondents who did prevention behaviour and suffering dengue 9.7%. Therefore, there should be improvement of information to public to pay attention of environmental conditions, active participation of all components society for prevention and support from government in prevention of dengue fever, give motivation to health service providers to support the implementation of the eradication of aedes aegypti mosquitoes.